The Impact Of Social Stigma On Humanity And Human Rights As Represented In The Film Atas Nama Daun (2022) - Priyoto, Priyoto; Pratama, Yoga; Noviana, Noviana (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
Film documents In the Name of Leaf (2021) tells the true story of Fidelis Arie Sudewarto, an Indonesian citizen who had to face social stigma and criminalization for using medical marijuana to treat his wife who suffered from a rare disease. This study aims to analyze the impact of social stigma on Fidelis' human rights as depicted in the film atas nama daun (20222).The method used is a descriptive qualitative method with content analysis techniques. Data were obtained through film transcription and analyzed by classifying Fidelis' human rights violations into three categories of rights: civil and political rights, economic, social and cultural rights, and collective and solidarity rights.The results of the study show that the social stigma received by Fidelis not only caused violations of civil and political rights such as loss of fair legal treatment, but also had an impact on economic, social, and cultural rights such as the loss of the role as head of the family and the destruction of family welfare. In addition, the stigma also robbed collective rights and solidarity, both for Fidelis and for the community of medical marijuana fighters in Indonesia.This study recommends the importance of humanitarian-based policy advocacy in handling similar cases, as well as protecting the rights of marginalized communities who are stigmatized in Indonesia